STRUKTUR ILMU DAN STRUKTUR TEORI BIMBINGAN DAN KONSELING - Rahman, Fadhila; Kemala, Intan Nurul; Kartawiria, Hendriyani Oktavia (JIEGC Journal of Islamic Education Guidance and Counselling, 2022)
Structure is the way something is arranged and built with a certain pattern. The structure in a science and theory is an important part, explaining how a science and theory is built. Structure plays a role in clarifying the boundaries of concepts in a science. Reviewing Guidance and Counseling from science through the structure means classifying the scientific concepts of Guidance and Counseling based on structural aspects, namely, objects, statements, propositions, main characteristics and systematics. Reviewing the theory of Guidance and Counseling can be done by analyzing the five aspects of the structure in various counseling approaches and techniques. Research as a way to develop science and theory must also have a complete structure so that the research results have a clear and systematic concept